Inversion and analysis of transparency changes in the eastern coastal waters of China from 2003 to 2023 by an improved QAA-based method - Cao, Shuhui; Xiao, Fei; Chen, Miaomiao; Wang, Zhou; Luo, Jiahuan; Du, Yun (Frontiers in Marine Science, 2024)
Transparency (𝑍𝑠𝑑 can most intuitively reflect changes in marine ecosystems, therefore, the data of 𝑍 𝑠𝑑 is crucial to protect marine ecosystems. However, there is still a relative lack of long-term sequence data on 𝑍 𝑠𝑑 for coastal turbid waters.an efficient means of obtaining long-term, large-scale 𝑍 𝑠𝑑 . The method proposed by Lee et al. (2015 is currently one of the most widely used methods, which is divided into clear water and turbid water models based on the 670 nm remote sensing reflectance ( 𝑅𝑟𝑠 . In this study, we employed an improved model building upon the aforementioned method. The improved model simulates the continuous transition from clear to turbid water, which allows for automatic adjustment of model weights based on a logistic curve. Utilizing this improved model, this study inverts 𝑍 𝑠𝑑 within 100 km of the eastern coast of China from 2003 to 2023 using MODIS Aqua Level 2 𝑅 𝑟𝑠 data. 𝑍𝑠𝑑 shows an increasing trend with the distance from the coast, with high 𝑍 𝑠𝑑 in the northern Yellow Sea, the southern Shandong Peninsula, and the far shore of the East China Sea, and the low 𝑍 𝑠𝑑in the coast of Bohai Sea and northern Jiangsu. As for the long-term changes, the number of pixels with significantly increased 𝑍𝑠𝑑 and those with significantly decreased 𝑍𝑠𝑑 and no significant changes accounted for 20.84%, 1.14% and 78.02%, respectively. The order of seasonal 𝑍 𝑠𝑑 is summer > autumn > spring > winter, and the seasonal variability amplitude increases synchronously with the offshore distance of seawater on the whole. Interestingly, the correlation between 𝑍𝑠𝑑 and the annual runoff of rivers exhibits spatial differentiation among six typical estuaries: there are positive correlations in northern, whereas negative correlations in the south.Additionally, the 𝑍 𝑠𝑑 in five of six estuaries have negative correlations with annual sediment transport. Overall, this study not only provides more accurate and continuous data of 𝑍𝑠𝑑 for nearshore turbid waters compared to those obtained by the original model, but also offers valuable insights on the spatiotemporal variation in the 𝑍𝑠𝑑 of large-scale seawater.